2010
DOI: 10.1371/journal.pone.0015580
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Induction of the Human Antimicrobial Peptide Cathelicidin in the Urinary Bladder

Abstract: The urinary tract is frequently being exposed to potential pathogens and rapid defence mechanisms are therefore needed. Cathelicidin, a human antimicrobial peptide is expressed and secreted by bladder epithelial cells and protects the urinary tract from infection. Here we show that vitamin D can induce cathelicidin in the urinary bladder. We analyzed bladder tissue from postmenopausal women for expression of cathelicidin, before and after a three-month period of supplementation with 25-hydroxyvitamin D3 (25D3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 35 publications
6
121
0
4
Order By: Relevance
“…Neutrophil release of the peptide ensures a rapid increase in the local concentration upon bacterial presence until epithelial production is increased for further protection (9). Expression can be increased by vitamin D (10). It is known that Camp Ϫ/Ϫ mice, lacking mCRAMP, the mouse homologue of human LL-37, have more E. coli bacteria attached to the bladder than wild-type mice, indicating an important role of this peptide in protection against urinary tract infections (7).…”
mentioning
confidence: 99%
“…Neutrophil release of the peptide ensures a rapid increase in the local concentration upon bacterial presence until epithelial production is increased for further protection (9). Expression can be increased by vitamin D (10). It is known that Camp Ϫ/Ϫ mice, lacking mCRAMP, the mouse homologue of human LL-37, have more E. coli bacteria attached to the bladder than wild-type mice, indicating an important role of this peptide in protection against urinary tract infections (7).…”
mentioning
confidence: 99%
“…Recent data show that other extrarenal tissues, such as the skin, prostate, lung, and gastrointestinal tract, but also macrophages and monocytes, express CYP27B1 locally (25,33,42), indicating that vitamin D exerts its actions beyond bone mineralization and could play a role in pathological conditions. In bronchial epithelial cells, 25D 3 is converted by the locally expressed CYP27B1 into its active metabolite, 1,25D 3 , which binds the vitamin D receptor (VDR) (25,28). Subsequently, the 1,25D 3 -VDR complex binds to the retinoic X receptor, moves to the nuclei, and binds to vitamin D response elements present in the promoter regions of genes important for recognition and defense against microbes, such as those encoding hCAP18/LL-37, human ␤-defensins 2 (hBD-2), NGAL, and CD14 (34,43,56).…”
mentioning
confidence: 99%
“…Recent studies have indicated that vitamin D plays a vital role in modulating the host immune response to infection. For example, vitamin D can stimulate production of antimicrobial peptides (AMPs) such as α-defensins, β-defensins, and cathelicidin [14,15]. Aside from their direct microbicidal role, AMPs modulate many other immune processes, including mast cell degranulation, cell differentiation, vascular permeability, and the process of antigen presentation [16,17].…”
Section: Discussionmentioning
confidence: 99%